Advances in gyroscope technologies - Armenise, Mario N. (Springer, 2011)
This monograph collects and critically reviews the main results obtained by the scientific community in gyroscope technologies research field. It describes architectures, design techniques and fabrication technology of angular rate sensors proposed in literature. MEMS, MOEMS, optical and mechanical technologies are discussed together with achievable performance. The book also consideres future research trends aimed to cover special applications. The book is intended for researchers and Ph.D. students interested in modelling, design and fabrication of gyros. The book may be a useful education support in some university courses focused on gyro technologies.